Enantiopure synthesis of [5]helicene based molecular lemniscates and their use in chiroptical materials - Leah E. M. White; Tiberiu-M. Gianga; Fabienne Pradaux-Caggiano; Chiara Faverio; Andrea Taddeucci; Henry S. Rzepa; Christian Jonhannesen; Lauren E. Hatcher; Giuliano Siligardi; David R. Carbery; G. Dan Pantoș (Nature Communications)
Abstract The ability to synthesise lemniscular molecules to allow for the study and application of their chiroptical properties is a notable technical challenge. Herein, we report the design and synthesis of enantiomers of a [5]helicenoid derived molecular lemniscate, in which two homochiral helicenes are linked via the formation of two azine motifs. We demonstrate that these molecules, and their helicenoid constituents, are also excellent chiral dopants that induce dissymmetry in the ground and excited states of the achiral emissive polymer F8BT, leading to high CPL activity. The ability to control the handedness of the helicenoid dopants via enantiopure synthesis affords control of the sign of CP emission. This manipulation of circularly polarised light is of great interest for optoelectronic technologies.